2019
DOI: 10.3390/genes10100769
|View full text |Cite
|
Sign up to set email alerts
|

Non-Random Distribution of Reciprocal Translocation Breakpoints in the Pig Genome

Abstract: Balanced chromosome rearrangements are one of the main etiological factors contributing to hypoprolificacy in the domestic pig. Amongst domestic animals, the pig is considered to have the highest prevalence of chromosome rearrangements. To date over 200 unique chromosome rearrangements have been identified. The factors predisposing pigs to chromosome rearrangements, however, remain poorly understood. Nevertheless, here we provide empirical evidence which sustains the notion that there is a non-random distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 27 publications
0
36
1
Order By: Relevance
“…In pigs, Grahofer et al [5] have successfully refined the breakpoint location of an segregating RT causing malformed piglets using sequence data of an unbalanced and balanced sib. Donaldson et al [18] showed that translocation breakpoints are nonrandomly distributed across cytogenetic bands, they are more prevalent on longer cytogenetic bands, gram negative bands, and common fragile sites. Investigating the sequence around breakpoints will enhance the detection and characteristics of translocation hotspots in the genome.…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, Grahofer et al [5] have successfully refined the breakpoint location of an segregating RT causing malformed piglets using sequence data of an unbalanced and balanced sib. Donaldson et al [18] showed that translocation breakpoints are nonrandomly distributed across cytogenetic bands, they are more prevalent on longer cytogenetic bands, gram negative bands, and common fragile sites. Investigating the sequence around breakpoints will enhance the detection and characteristics of translocation hotspots in the genome.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the chromosome 6 appears to be particularly prone to be involved in reciprocal translocation, resulting within the highest tertile for the number of observed breakpoints (Donaldson et al, 2019). However, the presence of these chromosomal hotspots seems to be distributed in a non‐random way and associated with the length of chromosomal band, chromatin density and presence of fragile sites (Donaldson et al, 2019; Riggs, Kuczek, Chrisman, & Bidwell, 1993; Rønne, 1995). In this respect, both SSC3 and SSC6 are characterised by common fragile sites (Rønne, 1995) that fall at the same band level (3p14) of the reciprocal translocation observed in the present study for SSC3, and in a very close proximity (6q28) for SSC6.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent chromosomal abnormality in pigs is the balanced reciprocal translocation (rcp; Ducos et al, 2008), which represents about 90% of the rearrangements described in literature (Rothschild & Ruvinsky, 2011). Up to date, over 190 different types of rcp have been identified, in particular in commercial breeds (Donaldson, Villagomez, Revay, Rezaei, & King, 2019; Raudsepp & Chowdhary, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The domestic pig karyotype is characterized by a tendency for an increased incidence of heritable, balanced structural chromosomal rearrangements such as reciprocal, Robertsonian, and tandem translocations, as well as paracentric and pericentric inversions. They are caused by spontaneous breakages of unstable chromosomal regions induced by adverse environmental factors [17,18]. These aberrations alter chromosome morphology (generally without loss of genetic material and without phenotypic changes), and their carriers show poorer reproductive performance compared to the herd average [1,19].…”
Section: Pig Karyotype Abnormalities and Their Effect On Carrier Fertmentioning
confidence: 99%